The temporal characteristics of seizures in neonatal hypoxic ischemic encephalopathy treated with hypothermia. (December 2015) - Lynch, Niamh E.; Stevenson, Nathan J.; Livingstone, Vicki; Mathieson, Sean; Murphy, Brendan P.; Rennie, Janet M.; Boylan, Geraldine B.
Highlights: We examine characteristics of EEG seizure in neonates with HIE and treated with Therapeutic Hypothermia. The burden, duration, number, intensity and distribution are calculated. The temporal characteristics of neonatal seizures are highly variable. Abstract: Purpose: The characteristics of electrographic seizures in newborns with hypoxic-ischaemic encephalopathy (HIE) treated with therapeutic hypothermia (TH) are poorly described. This retrospective, observational study provides reference data on the characteristics of seizures and their evolution over time in newborns with HIE receiving whole-body TH. Method: The cohort under analysis included 23 infants with HIE and seizures defined by multi-channel EEG recordings. Clinical presentation, details of TH and antiepileptic drugs used were recorded. Time from first to last-recorded electrographic seizure (seizure period) was calculated. Temporal characteristics of seizures – total burden, duration, number, burden in minutes per hour, distribution of burden over time (temporal evolution), time from seizure onset to maximum seizure burden ( T msb ), T 1, and time from T msb to seizure offset, T 2 – were analysed. Results: The median age at electrographic seizure onset was 13.1 h (IQR: 11.4 to 22.0). T msb was reached at a median age of 19.4 hours (IQR: 12.2 to 29.7). Median seizure period was 16.5 h (IQR: 7.0 to 49.7), median number of seizures per hour was 1.9 (IQR: 1.0 to 3.3). The seizure burden was 4.0 min/h (IQR: 2.0 to 7.0). There was no consistent pattern in the temporal evolution of seizures in neonates treated with TH. The skewness was neither positive nor negative ( p -value = 0.15), there was no difference between the duration of T 1 and T 2 ( p -value = 0.09) and no difference in the seizure burden between T 1 and T 2 (p = 0.09). There was an association between T msb and Phenobarbital (PB) administration ( r = 0.76, p -value < 0.001). Conclusion: There is no consistent temporal evolution of seizure burden in neonates treated with TH. Seizures are diffuse, and their characteristics are variable.